Laterally-actuated inside-driven RF MEMS switches fabricated by a SOG process. (12th May 2015) - Wang, Li-Feng; Han, Lei; Tang, Jie-Ying; Huang, Qing-An
Abstract: This paper presents two RF MEMS switches, both of them are laterally-actuated and inside-driven. One is the push–pull type switch controlled by only one actuation signal, and the other is the low voltage three-state switch actuated by rhombic structures. To fabricate RF MEMS switches, the silicon on glass (SOG) based microwave transmission line is redesigned, and an electroplated gold layer is added to the standard SOG process flow. The measured insertion loss and isolation of the push–pull type switch at 6 GHz are −0.28 dB and −38.4 dB, respectively, and its measured pull-in voltage is 57 V. The measured insertion loss and isolation of the low voltage three-state switch at 6 GHz are −0.77 dB and −53 dB, respectively, and the measured pull-in voltage is only 15 V. Preliminary lifetime tests show the lifetimes of both switches exceed the magnitude of 10 7 cycles.